Communication In Shaping The Work Culture Of Bulog Employees In The Regional Office Of Bengkulu - Astari, Indra Dini; Sari , Sapta; Endang , Anis (CV. Era Digital Nusantara, 2024)
Perum BULOG Bengkulu Regional Office is one of the large state-owned companies, the importance of this company to develop both the government and all levels working in it. The purpose of this study is to explain how to communicate employees in shaping the work culture of Perum Bulog Bengkulu employees. This research focuses on the communication patterns that exist in it so as to shape the current work culture of employees at the Bengkulu Regional Office of Perum Bulog using transactional theory, on 3 indicators of micro, macro and individual approaches. This research uses a qualitative method with a descriptive approach and purposive sampling technique by conducting direct interviews with 6 informants with criteria such as gender, age, position to employee tenure. The results of this study explain that communication at Perum Bulog Bengkulu Regional Office is described as a dynamic process with a free-flowing flow where Perum Bulog Bengkulu Regional Office upholds openness and smooth communication between employees. This is what makes transparency in communication between employees so that all parties can freely access the information needed to carry out their respective duties. The company shows a commitment to building an inclusive culture for all employees. This inclusive culture can be seen from the existence of equal opportunities, support for self-development, objective performance appraisal. There are various benefits for the company with this inclusive culture, such as employee motivation and enthusiasm, improving employee skills, employee knowledge and creating a positive and pleasant work environment.